Separation and photoluminescence study of single-walled carbon nanotubes - Chen, Fuming. (2011)
Single-walled carbon nanotubes (SWNTs) can be described as a roll-up of graphene sheet into a hollow cylinder with diameters in a nanometer range and lengths varying from tens of nanometers to centimeters. Owing to its different roll-up chirality, the electronic property of SWNTs exhibits either metallic or semiconducting behaviour, and the coexistence of nanotubes with various chiralities in commercial SWNTs products has been a tremendous bottleneck for SWNTs fundamental research, fabrication toward high performance devices. It is therefore desirable to develop the nanotubes separation methods that allow us to obtain pure metallic or semiconducting nanotubes, even some chiral specific SWNT samples. In this thesis, we mainly developed a new separation technology of SWNTs based on polymers wrapping, high to ~79% purity of (7, 5) SWNTs can be achieved if narrow diameter distribution SWNTs is used. We also find that energy can be transferred from these photo excited polymers to SWNTs, and between SWNTs, these were monitored by photoluminescence excitation mapping. As an application, SWNTs-polymer hybrids can be used as a photon-detector with enhanced photo current.